Environmental and climate innovation: Limitations, prices and policies - Jeroen C. J. M. van den Bergh (Max Planck Institute of Economics, 2010)
There is currently much hope about environmental innovation and green technologies, notably as a response to the threat of climate change. This paper offers a critical perspective on the role of technological innovation to solving environmental problems, based on considering empirical economic studies, energy and environmental rebound, the energy return on energy investment (EROEI) of alternative energy technologies, and various crowding out effects. Features of green technologies and motives of green innovators are briefly discussed. This is followed by an examination of the desirable mix of environmental and innovation policies to stimulate environmental innovation, to escape current and to evade early new lock-ins, and to avoid the occurrence of a green paradox. This involves an evaluation of specific policy instruments from an environmental innovation angle. An extended argument is offered to clarify that environmental (CO2) pricing is crucial - even though insufficient - for environmental innovation to deliver definite solutions. In other words, environmental innovation (policy) is no substitute for environmental regulation (through prices). The paper also discusses the importance for environmental innovation of international agreements for regulation of greenhouse gas emissions and international coordination of innovation efforts.
urn:nbn:de:gbv:27-20110630-110555-7
Keywords: 330; climate change; environmental regulation; EROEI; green paradox; rebound; sustainability transition; technological diversity; Klimaschutz; Umwelttechnik; Innovation; Innovationspolitik; Ökosteuer; Wirkungsanalyse; Klimaveränderung; Theorie